An empirical study on computer literacy among Bachelor of Accountancy graduating students in Malaysian public higher institutions / Siti Noor Hayati Mohamed Zawawi and Rashidah Abdul Rahman - Mohamed Zawawi, Siti Noor Hayati; Abdul Rahman, Rashidah (Faculty of Accountancy, 2003)
Information age in the 21st century is witnessing the dramatic increase in computerrelated jobs. Many employers are now recruiting candidates who have knowledge and experience in information technology or those who are computer literate. Therefore, potential candidates should master at least some level of computer literacy. Thus, the main objective of this study is to analyse the level of computer literacy among graduating Bachelor of Accountancy students in Malaysian public higher institutions. Based on the findings, computer literacy can be group into basic, advanced, self-efficacy and technical level. Evidence shows that, graduating accountancy students are computer literate at the basic, advanced and self-efficacy level. Significant difference is also found in the students' perceptions on Accounting Information System (AIS) suggesting that the educators should give due attention to AIS courses, particularly in enhancing students' computer literacy level. There are also evidence that the level of basic and advanced computer literacy of male students are significantly higher than female students; those who owned computers are significantly more computer literate in terms of basic and advanced computer literacy than those who did not own computers; and finally, previous computer experience is not generally related to computer literacy achievement, except for self-efficacy computer literacy level.